Spontaneous Hemoperitoneum in Pregnancy - Gonçalves, Daniela (2019)
Endometriosis is a benign, estrogen-dependent chronic disorder. Pregnancy is considered to have a positive effect on endometriosis due to blockage of ovulation; however, evidence is emerging on the role of endometriosis not only in infertility but also in poor pregnancy outcomes. We present the case of a pregnant woman admitted for sudden and severe abdominal pain at 34 weeks gestation. Her previous medical history included endometriosis suspected by clinical symptoms and ultrasound. During cesarean section, performed by sustained fetal bradycardia, a large volume hemoperitoneum and multiple hemorrhagic foci in the posterior uterine wall were detected. Although rare, spontaneous hemoperitoneum may occur in pregnancy, especially in women with endometriosis. Thus, a prompt suspicion and expedite intervention are needed to improve maternal and fetal outcomes.